Malasseziosis dan otitis eksterna bersamaan pada seekor pug senior - Ni Made Santi Rahayu Adiari; Putu Ayu Sisyawati Putriningsih; Sri Kayati Widyastuti (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2025)
Dermatitis is a common skin disorder in dogs, caused by a variety of factors including fungi, ectoparasites, bacteria, and metabolic diseases. This case report describes a 7-year-old male pug with dermatitis associated with Malassezia infection and concurrent otitis externa caused by bacterial and Malassezia infections. The dog exhibited clinical signs, including pruritus, erythema, scaling, hyperpigmentation, lichenification, malodor, oily coat, and wet, malodorous ear discharge. Cytological analysis of skin and ear samples, performed using acetate tape preparation and otic swabs, revealed the presence of Malassezia yeast and cocci-shaped bacteria. Hematological evaluation revealed normocytic normochromic anemia. Based on these findings, the dog was diagnosed with Malasseziosis and bacterial-Malassezia otitis externa. A comprehensive therapeutic regimen was implemented, including oral antifungal ketoconazole, sebazole shampoo, oticon ear drops, anti-inflammatory methylprednisolone, antihistamine chlorpheniramine maleate, and supportive supplementation with multivitamins (Livron B-plex) and fish oil. After 21 days of treatment, significant clinical improvement was observed, demonstrating the efficacy of this multimodal therapeutic approach.